Complexity Of Annual License Notification Of Small-Medium Tax Business Taxes - Rahayu Asriyani; Agus Bandiyono (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
The issuance of Government Regulation 23 of 2018 is the government’s effort to encourage the growth of MSMEs while simultaneously increasing MSME compliance in the taxation field. This study aims to analyze the complexity of the SME Annual Taxpayer Individual Taxpayers. This quantitative study uses a questionnaire with the UMKM Individual Taxpayer in Pondok Aren Tax Office as the respondent. Pondok Aren KPP was chosen as a research location because it is an KPP that intensively approaches UMKM. This study uses the SPT complexity variable as the dependent variable. While the independent variables are ambiguity, SPT calculation, rule details, rule changes, taxpayer accounting and tax return forms. Based on the results of the study, there are 3 variables that significantly affect the complexity of the MSME Annual Taxpayer Personal Taxpayers, these variables are the calculation of tax returns, detailed rules and rules changes.